A Turnover in the Radio Light Curve of GW170817 - Dobie, D.; Kaplan, D.; Murphy, T.; Lenc, E.; Mooley, K.; Lynch, Christene; Corsi, A.; Frail, D.; Kasliwal, M.; Hallinan, G. (Institute of Physics Publishing, 2018)
We present 2-9 GHz radio observations of GW170817 covering the period 125-200 days post-merger, taken with the Australia Telescope Compact Array (ATCA) and the Karl G. Jansky Very Large Array (VLA). Our observations demonstrate that the radio afterglow peaked at 149 ±2 days post-merger and is now declining in flux density. We see no evidence for evolution in the radio-only spectral index, which remains consistent with optically thin synchrotron emission connecting the radio, optical, and X-ray regimes. The peak implies a total energy in the synchrotron-emitting component of a few × 1050erg. The temporal decay rate is most consistent with mildly or non-relativistic material and we do not see evidence for a very energetic off-axis jet, but we cannot distinguish between a lower-energy jet and more isotropic emission.